British or American English?: A handbook of word and grammar patterns - Algeo, John (Cambridge University, 2014)
Containing extensive quotations from real-life English on both sides of the Atlantic, collected over the past twenty years, this is a clear and highly organized guide to the differences - and the similarities - in the grammar of British and American speakers. Written for those with no prior knowledge of linguistics, it shows how these grammatical differences are linked mainly to particular words, and provides an accessible account of contemporary English as it is actually used.